Orexin, orexin receptor antagonists and central cardiovascular control - Carrive, Pascal (Frontiers in Neuroscience, 2013)
Orexin makes an important contribution to the regulation of cardiovascular function. When injected centrally under anesthesia, orexin increases blood pressure, heart rate and sympathetic nerve activity. This is consistent with the location of orexin neurons in the hypothalamus and the distribution of orexin terminals in the central autonomic network. Thus, the two orexin receptors, Ox1R and Ox2R, which have partly overlapping distribution in the brain, are expressed in the sympathetic preganglionic neurons of the thoracic cord as well as in regions such as the pressor area of the rostral ventrolateral medulla. Both Ox1R and Ox2R appear to contribute to the cardiovascular effects of orexin, although Ox1R is probably more important. Blockade of orexin receptors reduces the cardiovascular response to certain stressors, especially psychogenic stressors such as novelty, aggressive conspecifics and induced panic. Blockade of orexin receptors also reduces basal blood pressure and heart rate in spontaneous hypertensive rats, a model of essential hypertension. Thus, there is a link between psychogenic stress, orexin and elevated blood pressure. The use of DORAs and SORAs may be beneficial in the treatment of certain forms of hypertension.